Genetic variation among 481 diverse soybean accessions, inferred from genomic re-sequencing - Babu Valliyodan (Nature Portfolio, 2021)
Measurement(s) genetic variation • SNP • Linkage Disequilibrium Technology Type(s) DNA sequencing • bioinformatics analysis • computational phylogenetic analysis Sample Characteristic - Organism Glycine soja • Glycine max Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13568552